Ex-Military Commissioners and Firm Performance: The Case of Indonesia Manufacturing Companies - Natalia, Irene; Isnalita, Isnalita (Gadjah Mada International Journal of Business, 2025)
This investigation relates to the new corporate governance (CG) suggestions that using ex-military commissioners can lead to better firm performance. Quantitative analysis was used to analyze the sample of manufacturing sector public companies. The data comprised 906 firm-years (from 2016 to 2021). This study shows that companies whose CG practices involve employing ex-military officers exhibit high firm performance levels. This study emphasizes the value of using a configurational analytical approach to explore firm jointly- and country-specific CG practices that engage firms to achieve the necessary level of performance. The current study calls policymakers’ attention to evalu- ating the current state of regulatory and competitive development in their countries and establishing policies in line with that assessment. The methodology provides connec- tions between firm performance and CG with retired military commissioners. This study broadens the focus of CG studies to provide effective solutions for practitioners, especially Indonesian manufacturing firms. It also highlights the importance of ex-military commis- sioners in a particular company sector and CG procedures specific to a particular nation. It encourages enterprises to reach the desired level of performance. The research impli- cation relates to good governance in board diversity using ex-military as independent commissioners for supervisory roles.